Educating the global citizen or the global consumer?. (October 2020) - Kramsch, Claire
Abstract: In this paper I review three models of language that have dominated language learning and teaching in the last 40 years: the textual model, the information exchange model, and the multilingual model. I analyze each one and consider how it stacks up to instances of language use in a globalized world. I then propose moving beyond the metaphors of citizens and consumers, and consider language teaching as educating denizens of a global ecology that requires sensitivity to context, political awareness, ethical answerability and a good dose of situational cunning.